INFORMATION GAP ON DISABILITIES: LIBRARY ROLE - Dr. Khalid Abdul Wahid,; Zaila Idris,; Norfitriah Bt Mat Seman,; Annisa Nana Nadhea,; Dewi Nauliafajrin, (Journal of Islamic, Social, Economics and Development, 2023)
Today, the large number of people with disabilities who are still unemployed is a problem that is important enough to be addressed immediately. Moreover, people with disabilities also contribute to a higher poverty rate than non-disabled people. This is partly due to the information gap related to job vacancies between people with disabilities and non-disabled people. The research method used in this article is a literature review. The data collected from this article is data published in 2020 and taken from valid institutions, such as the Survei Sosial Ekonomi Nasional (Susenas), the Badan Pusat Statistik (BPS), and the Badan Perencanaan Pembangunan Nasional (Bappenas). The findings are that the information gap is caused by internal factors in the form of physical or mental limitations experienced by people with disabilities and external factors in the form of many negative perceptions of people with disabilities. The presence of a social inclusion-based library as an information institution will be one solution to this problem. A social inclusion-based library is a library that proactively helps individuals and communities develop skills and confidence and helps improve social networks by utilizing the library's role, such as creating work programs, maximizing the use of technology, and others.